The Potential of Dark Tourism for Malaysian Tourism Industry: A Review - Ahmat, Norunnajjah; Ariffin, Hafzan; Abdul Hamid, Norfazilah (Journal of Human Capital Development (JHCD), 2021)
This is conceptual research on the potential of dark tourism as a new product in Malaysia. This is important because tourism industry is one of the largest earning sectors in Malaysia. However, Malaysia needs to offer a new product beside usual one relates to Friendly and Halal Country, Health tourism etc. This concept has grown widely in the West, Europe and even Australia. It may sound bad because it involves tragedies, disasters, violent and any dark side under the umbrella of heritage tourism context. Then, the objective of this research is important to review the potential of the concept of dark tourism as a new product in Malaysia. This product will enliven the local history or local stories which are ignored or abandoned or forgotten and even will be preserved as tangible and intangible heritage legacy. This is a library research approach with expectation that Malaysia needs a new product for its sustainability on tourism industry where dark tourism is one possibility.